2007
DOI: 10.2106/jbjs.f.01132
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Fixation Sites for Optimum Isometry of Posterolateral Reconstruction*

Abstract: A popliteus tendon or popliteofibular ligament reconstruction with the bone block centered over the femoral footprint of the popliteus tendon was highly non-isometric. If the graft were fixed at 30 degrees of flexion, it would elongate approximately 4 mm when the knee was extended to 0 degrees and possibly stretch out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…A majority of the studies on graft isometry has been performed on cruciate ligament reconstructions, and only recently have studies evaluated graft isometry on the posterolateral corner [18]. Graft isometry is important for any ligament reconstruction in order to effectively stabilize the joint during the entire range of motion.…”
Section: Discussionmentioning
confidence: 99%
“…A majority of the studies on graft isometry has been performed on cruciate ligament reconstructions, and only recently have studies evaluated graft isometry on the posterolateral corner [18]. Graft isometry is important for any ligament reconstruction in order to effectively stabilize the joint during the entire range of motion.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the length changes reported, the shortening of the posterior graft strand in the Arciero and LaPrade techniques restores varus and rotational stability in flexion as demonstrated biomechanically in previous studies. 10 , 27 Sigward et al 24 investigated the isometry of the PLC and found similar results for the FCL graft strand. They found that the most isometric femoral insertion for the FCL graft strand was in direct proximity (<2 mm) to the anatomic insertion, which could be confirmed by our findings.…”
Section: Discussionmentioning
confidence: 78%
“…This contradicts our findings and previous biomechanical findings that intend a taught PFL and PLT graft strand in flexion and suggested a tensioning in 30° 2 and 60°. 10 The contradicting finding is most likely the result of the chosen definition of the femoral popliteus insertion posterior to the FCL insertion by Sigward et al 24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sigward et al (27) determined the ideal isometric location for the grafts of the fibular collateral ligament, popliteus tendon and popliteofibular ligament in the lateral femoral condyle using the foot-print of the fibular collateral ligament and popliteus tendon, in accordance with the studies of Fanelli and Larson (26). We therefore believe that the anatomical reconstruction agrees with the concepts of isometry, and together, these ideas can provide the best results in reconstructions of the posterolateral corner of the knee.…”
Section: Discussionmentioning
confidence: 98%